National Institute of Health Stroke Scale Score Mediated the Relationship between Systemic Inflammatory Response Index, High-Sensitivity C-Reactive Protein, and Functional Prognosis of Acute Ischemic Stroke: A Prospective Cross-Sectional Study - Xueqing Liu; Tong Zhang; Liqin Yang; Guojuan Chen; Peng Ding; Delin Yu; Haibing Liao; Jing Liu; Wei Yue (Heart and Mind)
Background: The systemic inflammatory indicators were reported to relate to the functional prognosis of acute ischemic stroke (AIS). Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), systemic inflammatory response index (SIRI), and C-reactive protein (CRP) were independent risk factors for poor prognosis in AIS patients. However, systemic inflammatory indicators may be affected by stroke severity. We are aiming to explore the relationship among systemic inflammatory indicators, severity, and functional prognosis of AIS. Methods: Data came from a prospective, cross-sectional, single-center study. We evaluated AIS severity with the National Institute of Health Stroke Scale (NIHSS) score. We divided the systemic inflammatory indicators into systemic inflammatory biomarkers and related indices. The systemic inflammatory biomarkers included leukocyte count, neutrophil count, naive neutrophil count, monocyte count, lymphocyte count, basophilic granulocyte count, eosinophilic granulocyte count, and high-sensitivity CRP (hs-CRP). Related indices, which were derived from further calculations of systemic inflammatory biomarkers, included NLR (neutrophil count/lymphocyte count), PLR (platelet count/lymphocyte count), SII (platelet count × neutrophil count/lymphocyte count), and SIRI (monocyte count × neutrophil count/lymphocyte count). We used multivariate linear regression, logistic regression, sensitivity analysis, and mediation analysis to analyze the data. Results: There were 1,357 patients included. After adjusted by multiple factors, we found that NIHSS score had positive correlation with leukocyte count (P < 0.0001), neutrophil count (P < 0.0001), naive neutrophil count (P = 0.0064), monocyte count (P < 0.0001), NLR (P < 0.0001), PLR (P < 0.0001), SII (P < 0.0001), SIRI (P < 0.0001), and hs-CRP (P < 0.0001) and had negative correlation with lymphocyte count (P < 0.0001) and eosinophilic granulocyte count (P < 0.0001). However, NIHSS score was irrelevant to basophilic granulocyte count. After excluding 178 patients with hospital-acquired infection, the NIHSS score became irrelevant to naive neutrophil count and eosinophilic granulocyte count as well. When we adjusted for many factors without NIHSS score, there was still a certain degree of correlation between most systemic inflammatory indicators and poor functional prognosis. When we added NIHSS score to the model, only SIRI (P = 0.0306) and hs-CRP (P = 0.0096) were associated with poor functional prognosis. After mediation analysis, we found that NIHSS score mediated 81.23% of the relationship between SIRI and poor functional prognosis, and 55.10% of the relationship between hs-CRP and poor functional prognosis. Conclusion: NIHSS score influences the levels of systemic inflammatory indicators and mediates the relationship between systemic inflammatory indicators and functional prognosis of AIS. Among all systemic inflammatory indicators, SIRI and hs-CRP were better predictors of poor functional prognosis, especially hs-CRP.